Емульсійна олігомеризація вуглеводнів фракції С9 у присутності гідроген пероксиду та стеаратів металів - Субтельний, Р. О.; Оробчук, О. М.; Мельник, С. Р.; Дзіняк, Б. О.; Subtelnyi, R. O.; Orobchuk, O. M.; Melnyk, S. R.; Dzinyak, B. O. (Lviv Politechnic Publishing House, 2018)
Описано одержання вуглеводневих смол низькотемпературною емульсійною олігомеризацією вуглеводневої фракції С9 рідких продуктів піролізу. Встановлено вплив якісного і кількісного складу окисно-відновної системи гідроген пероксид – стеарат металу змінної валентності на перебіг емульсійної олігомеризації. Досліджено вплив солей купруму, стануму, цинку та нікелю стеаринової кислоти. Обрано оптимальну окисно-відновну систему ініціювання, що забезпечує одержання олігомери із найвищим виходом. Визначено залежність виходу і характеристик олігомерів вмісту стеарату стануму у реакційній суміші.

The hydrocarbon resins production by the low-temperature emulsion oligomerisation of the liquid pyrolysis products C9 hydrocarbon fraction of is described in this article. The influence of qualitative and quantitative composition of the oxidation-reduction system of hydrogen peroxide – metal stearate on the variable valency on the yield of emulsion oligomerization was established. The influence of copper, tin, zinc and nickel salt of stearic acid was investigated. An optimal oxidation-reduction system of initiation were selected to provide an oligomer with the highest yield. It was determined that the dependence of oligomer yield and characteristics of the stearate amount in the reaction mixture.
C9 fraction emulsion oligomerization in the presence of hydrogen peroxide and metal steerates
Keywords: емульсійна олігомеризація; вуглеводнева фракція; гідроген пероксид; олігомер; окисно-відновна система; emulsion oligomerization; hydrocarbon fraction; hydrogen peroxide; oligomer; oxidation-reduction system